2019
DOI: 10.24198/jaab.v2i1.20428
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Religiosity, Nationalism, and Tax Corruption Perception on Tax Compliance

Abstract: This study aims to determine the effect of religiosity, nationalism, and perceptions of tax corruption on MSMEs taxpayer compliance in the area of Bandung City. This research uses taxpayer awareness, moral obligation and quality of tax service as factors. A Questionnaire was used as research instruments in data collection. Respondents were sampled in this research are individuals who run businesses that belong to small and medium micro enterprises. Multiple linear regression with SPSS program version 23 is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 7 publications
1
7
0
12
Order By: Relevance
“…The higher the sense of taxpayer nationalism, the higher the level of taxpayer compliance. This result is in line with the findings of previous research, which also found that a sense of nationalism can improve tax compliance (Putri and Venusita, 2019;Darmawan, Mulyadi and Dahlan, 2020;Hanifah and Yudianto, 2019;Purnamasari, Pratiwi and Sukirman, 2017). This result also verifies that in addition to external motivation, internal motivation also plays a role in shaping the discipline of taxpayers.…”
Section: The Effect Of Nationalism Of Tax Compliancesupporting
confidence: 92%
See 2 more Smart Citations
“…The higher the sense of taxpayer nationalism, the higher the level of taxpayer compliance. This result is in line with the findings of previous research, which also found that a sense of nationalism can improve tax compliance (Putri and Venusita, 2019;Darmawan, Mulyadi and Dahlan, 2020;Hanifah and Yudianto, 2019;Purnamasari, Pratiwi and Sukirman, 2017). This result also verifies that in addition to external motivation, internal motivation also plays a role in shaping the discipline of taxpayers.…”
Section: The Effect Of Nationalism Of Tax Compliancesupporting
confidence: 92%
“…The results of previous studies revealed that the higher the nationalism of taxpayers towards their country, the more compliant the taxpayers with tax law (Putri and Venusita, 2019;Darmawan, Mulyadi and Dahlan, 2020;Hanifah and Yudianto, 2019;Purnamasari, Pratiwi and Sukirman, 2017). However, similar studies are still rare.…”
Section: The Effect Of Nationalism To Tax Compliancementioning
confidence: 98%
See 1 more Smart Citation
“…Research conducted by Kiha & Nenomnanu (2020); Sista (2019); Alhempi et al, (2020); Bachas et al, (2019); dan Purba et al, (2020) related to the characteristics of being accountable for taxpayer compliance. Chetisa Putri & Venusita (2019); Tambun & Haryati (2022); Hanifah & Yudianto, (2019); Mayapada et al, (2021); dan Idrus et al, (2020) linking the attitude of nationalism to taxpayer compliance.…”
Section: Intrductionmentioning
confidence: 99%
“…The mediating effect of national identification has never been studied in Indonesia, although there is evidence of the influence of nationalism (i.e. pride to be an Indonesian citizen) on taxpayer compliance (Hanifah & Yudianto, 2019;Purnamasari et al, 2018). Compliance with the law also concerns traffic rules, with the traffic police as the authority.…”
Section: Compliance With Laws (Tax and Traffic Rulementioning
confidence: 99%